TYPE 2 DIABETES MELLITUS AND SYSTEMIC ARTERIAL HYPERTENSION: ETIOLOGICAL, PATHOGENIC, AND PATHOPHYSIOLOGICAL ASPECTS - Wille, Daniele Fernanda; da Silva, Fernanda D’Avila; Quines, Caroline Brandão; Frizzo, Matias Nunes (Seven Editora, 2026)
Non-communicable chronic diseases represent a major challenge to public health due to their high prevalence, impact on morbidity and mortality, and association with modifiable risk factors such as physical inactivity, inadequate diet, smoking, obesity, and alcohol consumption. Among these diseases, systemic arterial hypertension and type 2 diabetes mellitus stand out because of their increasing frequency and direct relationship with cardiovascular, renal, and metabolic complications. Systemic arterial hypertension has a multifactorial etiology involving genetic predisposition, sympathetic hyperactivity, activation of the renin-angiotensin-aldosterone system, and endothelial dysfunction, whereas type 2 diabetes mellitus results from the interaction between insulin resistance, progressive pancreatic beta-cell dysfunction, and chronic low-grade inflammation. The diagnosis and monitoring of these conditions require careful clinical evaluation and specific laboratory tests, such as blood pressure measurement, fasting blood glucose, glycated hemoglobin, and oral glucose tolerance test. Treatment is based on lifestyle modification, the use of antihypertensive and antidiabetic drugs, as well as continuous follow-up in programs such as HIPERDIA. Therefore, an integrated understanding of these disorders is essential for adequate control, prevention of complications, and improvement of patients’ quality of life.